Computer modeling of Vilnius University finance management in a process of studies - Jurkus, Vytautas; Ivanauskas, Feliksas; Pikturna, Aleksas (Lietuvos matematikos rinkinys, 2023)
In this work a computer simulation of Vilnius University financial management is completed. The purpose of the simulation is to calculate optimal distribution of monetary reserves for each VU faculty. In addition, the conclusion is made, which budget is oriented to quality of studies and which has social aspect.
Keywords: modelling of university finance; higher education